The anonymously adopted child: Impact of age and parental psychopathology on adoptees' mental health. (December 2020) - Kernreiter, Jennifer; Klier, Claudia; Zeiler, Michael; Huscsava, Mercedes M.; Fiala, Christian; Felnhofer, Anna
Highlights: Older anonymously born adoptees had a higher overall problem score than the norm. Older anonymously born adoptees showed more externalizing behaviours than the norm. Younger adoptees had lower total problem scores than the norm. Adoptees' mental health was positively associated with age and parental mental health. Parents' anxious attachment style predicted adoptee's mental health problems. Abstract: Children and adolescents who have been anonymously adopted are an understudied subgroup of adoptees, particularly with regards to their mental health. Hence, the objective of this study was to assess whether the mental health of anonymously adopted children and adolescents differs from a representative norm population, with particular regards to age and gender specific norms. Additionally, possible predictors of anonymous adoptees' mental health, such as the adoptive parents' mental health, their attachment styles and demographic variables were evaluated. Data was collected between 2018 and 2019 using an online survey or paper pencil questionnaires (parents' choice). The sample consisted of 97 adoptive parents, who reported on their anonymously adopted children aged between 2 and 17 years using the Child Behavior Checklist (CBCL). Older adoptees born anonymously showed a higher overall score and more externalising behaviours, when compared to a representative German (non-adopted) reference norm population. The younger anonymously born adoptee group showed significantly lower overall, internalising and externalising behaviour problem scores in comparisons to the norm population. Child mental health problems were positively associated with parental mental health problems and children's age. Additionally, adoptive parents' anxious attachment style was a predictor for children's mental health problems. The current results imply that prevention and treatment of existing mental health problems should target the whole adoptive family and should be implemented by default in post-adoption services.